Membawa Rasa Keluar Desa Melalui Video Profil Tempe Mendoan Ikon Desa Sri Mulya - Antasari, Lyka; Devi, Puspita; Oktavia, Novelin; Kinanti, Gita Ayu; Triani, Shinta; Praja, Aji Ranu (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
This community service program aims to introduce tempe mendoan as a culinary icon typical of Sri Mulya Village to a wider market through digital media. Tempe mendoan which is traditionally produced using banana leaves as a wrapper and firewood as a cooking utensil reflects local wisdom that needs to be preserved. In this program, KKN students collaborate with local business actors to produce a tempe mendoan profile video. This video shows the process of making tempe mendoan from start to finish, with a focus on the uniqueness of the tradition that is maintained. The implementation method includes data collection, video shooting, editing, and uploading to a digital platform. The results of the activity show that the profile video uploaded via WhatsApp, Instagram and village YouTube social media has succeeded in increasing the appeal of tempe mendoan, which is indicated by an increase in orders from consumers outside the village. In addition, this program increases awareness of the village community about the importance of digital marketing in developing local products. The conclusion of this activity is that digital technology, especially profile videos, can be an effective means of preserving local culture while expanding economic opportunities. Furthermore, tempe producers can utilize e-commerce to expand their market and collaborate with restaurants or cafes as distribution partners. In addition, innovation in product variants such as ready-to-eat tempe mendoan packaging can increase sales value.Keywords: tempe mendoan, local wisdom, digital marketing